2015
DOI: 10.1080/21642850.2015.1088388
|View full text |Cite
|
Sign up to set email alerts
|

What distinguishes responders from nonresponders to a vocational rehabilitation program?

Abstract: Objective: The aim of the present study was to compare responders and nonresponders in terms of work ability (WA) to a multidisciplinary vocational rehabilitation program (MVRP) in Norway. Methods: The WA of 74 participants was tested at baseline and in the final week of a 4-6-week intervention. The participants whose WA increased were defined as WA-responders, whereas participants with no increases or with decreases in their WA after the intervention were defined as WA-nonresponders. Measures of functional he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…As shown in Table 1, WA-nonresponders did not enhance their mindfulness over the course of the program as measured by any facet of the FFMQ. A recently published study on this sample (Vindholmen, Haugen, Høigaard, & Seiler, 2015), revealed that, at baseline, the WA-nonresponders demonstrated significantly higher pain intensity level and lower sense of mastery than WA-responders. Therefore, it is possible that high pain intensity, low sense of mastery, or the combination of these two factors in the WA-nonresponder group at baseline made them less capable of learning and practicing mindfulness.…”
Section: Discussionmentioning
confidence: 72%
“…As shown in Table 1, WA-nonresponders did not enhance their mindfulness over the course of the program as measured by any facet of the FFMQ. A recently published study on this sample (Vindholmen, Haugen, Høigaard, & Seiler, 2015), revealed that, at baseline, the WA-nonresponders demonstrated significantly higher pain intensity level and lower sense of mastery than WA-responders. Therefore, it is possible that high pain intensity, low sense of mastery, or the combination of these two factors in the WA-nonresponder group at baseline made them less capable of learning and practicing mindfulness.…”
Section: Discussionmentioning
confidence: 72%